Pricing the exotic : path-dependent american options with stochastic barriers (2018)
"The use of currency options as an instrument of intervention in the foreign exchange market has been largely unexplored. In this document we develop a pricing strategy that allow us to value and examine the options issued by the Central Bank of Colombia during 1999-2012. The intuition behind this strategy is to approximate the value of an American option through a portfolio of European options with different maturities. The development of this technique is necessary due to the possible bias that standard numerical methods have in the context of these exotic options. The results of our model coincide with the bids and premiums observed during the option's auctions. Additionally, the option's greeks of our model allow us to conjecture about the portfolio channels through which these instruments could be effective." -- Tomado del Formato de Documento de Grado.